Direct detection of Borrelia burgdorferi spirochetes in patients with early disseminated Lyme borreliosis - Schwarzová, Katarína; Kost'anová, Zina; Holecková, Katarína; Spitalská, Eva; Boldis, Vojtech (Central European journal of public health, 2009)
The detection of spirochetes in 15 patients with clinically documented early disseminated LB has been analysed when using cultivation method of the plasma or the cerebrospinal fluid, electron microscopy, commercial Western blot and detecting the DNA of the pathogen in vitro cultures by PCR-RFLP. Spirochetes were isolated in eight blood and one cerebrospinal fluid culture samples. In seven cases (47%), previous serodiagnostic laboratory tests were negative. Borrelial DNA was detected by PCR in 67% patients (9 blood samples and 1 CSF sample). Using Msel restriction fragments of PCR products of the amplified rrf-rrl region, we identified Borrelia garinii (80%), one B. afzelii isolate and one B. burgdorferi s.s.
Keywords: Adolescent; Microscopy, Electron; Adult; Male; lidé; lidé středního věku; western blotting; Humans; Child; Lyme Disease; Middle Aged; elektronová mikroskopie; Serologic Tests; polymerázová řetězová reakce; lymeská nemoc; mužské pohlaví; dospělí; Polymerase Chain Reaction; dítě; ženské pohlaví; mladiství; sérologické testy; Borrelia burgdorferi; Female; Blotting, Western